Square Root - Type Control for Robot Manipulators. (15th January 2013) - Reyes, Fernando; Cid, Jaime; Limon, Miguel Angel; Cervantes, Manuel
This paper addresses the problem of position control for robot manipulators. A new control structure with compensation for global position is presented. The main contribution of this paper is to prove that the closed loop system of the nonlinear robot dynamics model and the proposed control algorithm is globally, asymptotically stable and in agreement with Lyapunov's direct method and LaSalle's invariance principle. Besides this, the theoretical results in a real-time experimental comparison are also presented to show a comparison of the performance between the square root type controller and simple PD scheme on a three degrees-of-freedom direct-drive robot.